2008
DOI: 10.1007/s10648-008-9095-2
|View full text |Cite
|
Sign up to set email alerts
|

A Cognitive Load Approach to Collaborative Learning: United Brains for Complex Tasks

Abstract: This article presents a review of research comparing the effectiveness of individual learning environments with collaborative learning environments. In reviewing the literature, it was determined that there is no clear and unequivocal picture of how, when, and why the effectiveness of these two approaches to learning differ, a result which may be due to differing complexities of the learning tasks used in the research and the concomitant load imposed on the learner's cognitive system. Based upon cognitive load… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
295
2
18

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 398 publications
(338 citation statements)
references
References 56 publications
5
295
2
18
Order By: Relevance
“…In addition, the transaction costs (communication and coordination within the group) should be kept to a minimum to ensure positive interdependence (Kirschner, Paas, & Kirschner, 2009). …”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In addition, the transaction costs (communication and coordination within the group) should be kept to a minimum to ensure positive interdependence (Kirschner, Paas, & Kirschner, 2009). …”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Kirschner et al showed that learning from "traditional" worked examples on a highly structured task (heredity problems) was more effective when done individually than collaboratively, whereas learning by solving conventional problems was more effective when done collaboratively than individually. They explained this in terms of the amount of cognitive load involved: because worked examples impose less cognitive load on individual learners than problem solving, the learning task can easily be performed by the individual, whereas problem solving imposes higher cognitive load, which can be shared by group members in collaborative learning situations (see also Kirschner et al 2009). In contrast, Chi et al showed that collaboratively observing a tutoring session and solving the same problems as the tutee in that session was more effective for learning than individual observation.…”
Section: For What Kinds Of Tasks Is Example-based Learning Effective?mentioning
confidence: 99%
“…In sum, CSCL environments should incorporate tools or mechanisms that offer students group awareness information to facilitate coordination and regulation of activities in both spaces. Such tools are called group awareness tools (Kirschner, Paas, & Kirschner, 2009;Van Bruggen, Kirschner, & Jochems, 2002).…”
Section: Using Group Awareness Toolsmentioning
confidence: 99%
“…Moreover, collaboration also requires coordination or regulation of activities in the relational space (cf., Yager, Johnson, Johnson, & Snider, 1986). During collaboration, group members have to discuss collaboration strategies, monitor collaboration processes, and evaluate and reflect on the manner in which they collaborated (Kirschner et al, 2009). …”
Section: Effects Of Using Group Awareness Tools On Online Collaborationmentioning
confidence: 99%